Penentu Tingkat Kunjungan Wisatawan pada Sebuah Objek Wisata - Tettie Setiyarti; Pipit Sundari; Ni Luh Nita Sulastrini; Ni Nyoman Nurani (Sekolah Tinggi Ilmu Ekonomi Semarang, 2021)
Abstract Tourist perception is important for tourism, where tourists can assess a tourist attraction and provide feedback that can be informed to other tourists. The main purpose of this article is to determine the effect of tourist perceptions and the completeness of tourist attractions on the level of tourist visits to a particular tourist site. The research that is used as the basis for writing this article uses Gunung Payung Cultural Park located in Kutuh Traditional Village, South Kuta District, Badung Regency, Bali as a case study. Data analysis techniques used include validity test, reliability test, multiple linear regression analysis, linearity test, normality test, heteroscedasticity test and multicollinearity test. The study found a positive and significant effect, both partially and simultaneously, between the independent variables (Tourist Perception and Completeness of Tourist Attractions) and the dependent variable (Tourist Visits Rate), which clearly indicates that the higher the Tourist Perception and Completeness of Tourist Attractions on a particular tourist site, the more the level of its tourist visits.